INTERNATIONAL COOPERATION OF NNGASU - THE PROJECTS REGARDLESS OF TIME AND POLITICS - Yuriy V. Philippov (Высшее образование в России)
This paper analyzes the characteristics and specificity of international cooperation of Nizhny Novgorod state university of architecture and civil engineering in educational and research spheres. The paper presents experience of implementing projects important for the region and the country. The article traces the dynamics of international cooperation of NNGASU since 1994 to the present moment.